Teaching anatomy of the lower extremity veins: Educational challenges - Marian Simka (Vascular Investigation and Therapy)
Recently, there has been a big progress in the understanding of anatomy of the lower extremity veins, resulting in the shift toward fascia-oriented topography of these blood vessels. Consequently, a new class of the interfascial veins of the lower limb has been distinguished. There were also important findings regarding the embryological development of these veins, which enabled an explanation of their high anatomical viability and their association with the nerves. These discoveries facilitated a wide use of the endovascular methods instead of open surgical techniques for the treatment of varicose veins and other venous pathologies. Yet, the undergraduate anatomical education is still based on old methods, primarily cadaver dissections, which seem to be inadequate in terms of teaching anatomy of the lower limb veins correctly and efficiently. In this review, it is discussed how anatomical classes for undergraduate medical students could be performed, taking into account not only recent anatomical and embryological discoveries but also findings in the field of cognitive psychology and educational sciences. It is suggested to augment the classes with “living anatomy” utilizing ultrasonography, to integrate anatomical topics with embryological ones, and to include into the curriculum anatomical variability, instead of a single anatomical pattern.